Pengaruh Capital Intensity, Related Party Transaction Dan Transfer Pricing Terhadap Tax Avoidance - Riska Oktafia; Mita Sicillia (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to analyze the influence of Capital Intensity, Related Party Transactions, and Transfer Pricing on Tax Avoidance. The study was conducted by analyzing the financial statements of companies in the primary consumer goods sector listed on the Indonesia Stock Exchange (IDX) for the period from 2019 to 2023. The sample consists of 24 companies with a total of 120 observations. The sampling method used is purposive sampling. The data used in this study are secondary data in the form of financial statements from each sampled company. The variables used in this study are Capital Intensity as the first independent variable, Related Party Transactions as the second independent variable, and Transfer Pricing as the third independent variable, with Tax Avoidance as the dependent variable. The panel data regression method was used as the methodology for this research. Data analysis was performed using Eviews 12 Student Version Lite software. The results indicate that the best model is the Fixed Effects Model (FEM). The research findings show that Capital Intensity, Related Party Transactions, and Transfer Pricing have a simultaneous effect on Tax Avoidance. Capital Intensity has a partial effect on Tax Avoidance, while Related Party Transactions and Transfer Pricing do not have a partial effect on Tax Avoidance.